Children, 'healthy' food, school and family: the '[n]ot really' outcome of school food messages. Issue 1 (2nd January 2020) - Maher, JaneMaree; Supski, Sian; Wright, Jan; Leahy, Deana; Lindsay, Jo; Tanner, Claire
ABSTRACT: This paper draws on a multi-method study with 50 families in Victoria, Australia. Primary school children were asked about food knowledge from school and whether they felt motivated to bring knowledge home. Generally, children and parents felt school food messages are unclear, contradictory and not relevant to them and this reduced the likelihood of messages coming home from school. We identify a critical difference in how families thought about healthy eating and food practices at home and the framework of school messages. Families focused on children's eating in a pragmatic way, infused with nurturance as well as concern. We argue their practices can be viewed as a form of relational consumption (Lindsay and Maher 2013. Consuming Families: Buying, Making, Producing Family Life in the Twenty-First Century . New York: Routledge.) where food is part of the everyday exchange of love and care. A disjunction exists between familial relational approaches and the regulatory framework of school food messages that impacts how messages move between these spaces. Attention to relational aspects of food consumption at school might allow for a more valuable exchange between family and schools that supports family endeavours to feed children well.